TRANFORMASI MATRIKS PADA RUANG BARISAN KONVERGEN - Wahidah Alwi (Teknosains, 2013)
The calculus have introduce the real functions namely for all functions to map real number to the real number. Now, the explanation it not only to real number but the mapping of norm space that is a linier transformations, namely the mathematical sentences with the mapping of a vector space to the others. The purpose of this research are how to know the requirements a infinite matrices in order to be a like as transformations in the sequences space is the sequences space c0 to c0. Matrices An x m can be looked as linier transformation of Rm to Rn. So the functions can map to point (x1, x2, x3, …, xm) at Rm to a point (y1, y2, y3,…, yn) at Rn. The similarly, a matrices can be looked as linier transformation of the sequences space to the others provided that line and coloum matrices that infinite elements. In this case, matrices map the sequences (x1, x2, x3, …) to the sequences (y1, y2, y3,…). This matrices is a infinite matrices. There for, the infinite matricres must fulfill several requirements in order be linier transformations of the sequences space to the certain sequences space, that is the infinite matrices A = (ank)n≥1 (k certain) with a finite suprimum can be linier transformation of the sequences c0 to c0.